Analisis Kestabilan Lereng dengan Metode Kesetimbangan Batas di Tebing Sungai Klawing, Kecamatan Kaligondang, Kabupaten Purbalingga, Jawa Tengah - Annisa, Hiskia Ulinuha; Yogi Adi Prasetya; Indra Permana Jati; Hanifah Hamna Lidia (Mataram University, 2025)
The Alluvium Formation on the hillside around the Klawing River, Kaligondang District, Purbalingga Regency, Central Java, experiences simultaneous landslides. This study examines the influence of lithology and erosion, which erodes the riverbanks, on the occurrence of landslides in the area. Field observations were conducted by determining the landslide position, identifying soil types, measuring slope geometry, determining slope layers, and collecting soil samples from each layer for further analysis. The Klawing River is highly prone to landslides due to its lithology, which is easily weathered and eroded, particularly in claystone and sandstone formations. Additionally, lateral erosion by the Klawing River erodes the slope foot, reducing the base support and increasing the potential for landslides. This research aims to analyze the slope safety factor in landslide-prone areas. The study focuses on the cliffs of the Klawing River, which are divided into three sections: upper, middle, and lower. Soil samples were collected and tested in the laboratory to determine parameters such as specific gravity, internal shear angle, and cohesion. Slope stability analysis was carried out using the Limit Equilibrium method (Morgenstern–Price) with the aid of Geostudio (Slope/W) software. The analysis results indicate the slope safety factor (SF) of the Klawing River, showing that the slope is in an unstable condition and highly susceptible to landslides.